Legal Aspects in Business Alliances and Strategic Partnerships Between Airlines - Suryawan, Ryan Firdiansyah; Juliater Simarmata (Dinasti Research, 2023)
The research explores the role of law in governing business alliances and strategic partnerships in the aviation industry, analyses its legal framework, its business implications, and provides policy recommendations. Qualitative methods are used by summarizing findings from several international scientific journals. The findings highlight legal aspects such as antitrust regulation, consumer protection, and liability towards employees. The importance of regulatory compliance for safe and fair operations is highlighted, as well as periodic reviews of legal responses. By strengthening understanding and implementation of legal aspects, the aviation industry can better address future challenges and safeguard the interests of stakeholders.